Time-domain optimization of amplifiers based on distributed genetic algorithms - Tavares, Rui Manuel Leitão Santos (2011)
Thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in the subject of Electrical and Computer Engineering